(untitled) - Smith, Glenn W. (Hoboken, N.J., 2004)
A compelling indictment of the Bush Administration's cynical, anti-democratic manipulation of the media
Keywords: Political culture,Manipulative behavior,Mass media,Political participation,Văn hóa chính trị,Tham gia chính trị,Thông tin đại chúng; Political aspects,Psychological aspects,Khía cạnh chính trị,Khía cạnh tâm lý,Khía cạnh chính trị; United States,United States,United States,United States